0002 An Orexin 2 Receptor-selective Agonist, TAK-925, Shows Robust Wake-promoting Effects In Mice And Non-human Primates. (27th April 2018) - Yukitake, H; Ishikawa, T; Suzuki, A; Shimizu, Y; Nakashima, M; Fujimoto, T; Rikimaru, K; Ito, M; Suzuki, M; Kimura, H
Abstract: Introduction: The orexin system is a critical regulator of sleep/wakefulness states, and the deficiency of orexin-producing neurons in lateral hypothalamus results in narcolepsy-like symptoms such as fragmentation of sleep/wakefulness and cataplexy-like episodes in other mammals, which are similar to those in patients. As narcolepsy-like phenotypes such as wakefulness fragmentation were observed in orexin 2 receptor (OX2R) knockout mice, but not in orexin 1 receptor (OX1R) knockout mice, activation of OX2R could be expected to promote wakefulness. In this study, we describe the pharmacological and electrophysiological characterization of an orexin 2 receptor-selective agonist TAK-925 in vitro and in vivo in wild-type mice and non-human primates. Methods: To determine the agonist activity of TAK-925, an in vitro calcium influx assay was conducted using Chinese hamster ovary cells stably expressing ProLink-tagged human OX2R and β-arrestin2-β-gal-EA fusion protein (hOX2R/CHO-EA cells). The effect of TAK-925 on OX2R downstream signals was evaluated in hOX2R/CHO-EA cells. Next, the effect of TAK-925 on endogenous OX2R was evaluated using whole-cell patch-clamp techniques in histaminergic neurons in mouse tuberomamillary nucleus (TMN). Last, the effect of TAK-925 on sleep/wakefulness states was evaluated in mice, common marmosets, and cynomolgus monkeys during their sleep phase. Results: TAK-925 activated OX2R (EC50 = 5.5 nM) in in vitro calcium influx assays with > 5, 000-fold selectivity against OX1R (EC50 > 30, 000 nM). An electrophysiological study revealed that TAK-925 activated physiological OX2R in histaminergic neurons in mouse TMN. TAK-925 significantly increased wakefulness time in wild-type mice (≥ 1 mg/kg, s.c.), common marmosets (≥ 0.1 mg/kg, s.c.), and cynomolgus monkeys (≥ 1 mg/kg, s.c.), but not in OX2R knockout mice, during their sleep phase. Conclusion: We demonstrated that OX2R-selective activation by TAK-925 induced wake-promoting effects in mice and nonhuman primates. Support (If Any): This work was conducted by Takeda Pharmaceuticals.